(untitled) (Huellas, 2025)
The paper addresses the conformation of tourist destinations in relation to geographical imaginaries associated with remote, unknown and unexplored places. The analysis focuses on the impact that the experience of the adventurer and explorer Yossi Ghinsberg has had on local tourism in the Bolivian Amazon. The analysis unfolds in three lines: 1) the definition of the narratives constructed around Ghinsberg’s experience and the geographical imaginaries implied in them; 2) the incidence of these narratives on the tourist attractions and activities in the destination; 3) Ghinsberg’s influence on the organization of tourist services in the area. The results show how certain traditional imaginaries associated with the Amazon are reinforced by tourism and how they coexist with different ideas fostered by local communities.